Analysis and Mitigation of Mismatch Errors in Rooftop Solar Panels - Balaji, C; Vyas, Abhishek; Dominic savio, A; Pugazhendiran, P (International Journal of Engineering and Technology, 2018)
Harnessing maximum power from solar Photo Voltaic (PV) is possible only with less power loss in the PV system. Interconnection of PV cells or modules with different properties create Mismatch losses. Mismatch losses are the series problem in PV systems under specific conditions. The effects of current mismatch of single (PV) modules are analyzed in literature, but only few investigations dealt the mismatch losses of a PV system, which also dictate the overall power output. In this paper, the performance of solar panels has been discussed based on the losses occurred in various panels. The efficiency of the power produced by panels will be affected by the mismatch error. The power produced by the roof top solar plant is monitored by solar edge monitoring system. In addition, methods to reduce the mismatch error in the solar panels are presented.Â
Keywords: PV Arrays; PV system; mismatch error; PV losses